USING THE SOLIDWORKS SOFTWARE PRODUCT FOR DETERMINING THE MASS, KINEMATIC AND DYNAMIC CHARACTERISTICS OF THE MOVEMENT OF OBJECTS OF A COMPLEX VOLUME GEOMETRICCONFIGURATIONS - HOROKHOVSKYI, VIKTOR; HORDIEIEV, ANATOLYI (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The work deals with the issue of engineering analysis of technical systems by means of computer modeling, in particular, the calculation of kinematic and dynamic characteristics of machine tools, cutting tools, wheeled vehicles using the SOLIDWORKS engineering analysis system, which allows conducting numerical experiments to determine their characteristics, namely mass, coordinates of the center of gravity for the purpose of further optimization according to various criteria. The paper analyzes the possibilities of various software products for solving the scientific and technical task of static balancing in the process of designing and determining the critical speeds of movement of complex multi-mass and multi-body systems. A computer modeling methodology in SOLIDWORKS is proposed to solve the problems of static balancing of multi-mass and multi-body systems in the process of their design. its location with further verification of the accuracy of the performed calculations of the location of the coordinates of the center of gravity of the complex system after carrying out static balancing. A methodology for determining critical traffic parameters is proposed, taking into account the weight of the vehicle, the type of cargo and its location in the body, the number of passengers, which provides an accurate determination of the center of gravity and its coordinates. In further studies, it is proposed to carry out simulations and calculations for specific parameters of complex multi-mass objects and to compare them with the results of calculations based on the recommended values of the coordinates of the center of mass.
Keywords: kinematics; static balancing; center of gravity coordinates; computer simulation